The Effect of Pod Age Development of Some Cocoa Clones to the Expression of Pod Characteristics Related to Cocoa Pod Borer (CPB) Resistance - Agung Wahyu Soesilo; Woerjono Mangoendidjojo; Witjaksono Witjaksono; Surip Mawardi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2008)
This paper reports the effect of cocoa pod development on the performance of pod characteristics which affects to Cocoa Pod Borer resistance. Four cocoa clones performing different response to CPB infestation, namely KW 514 (resistance), ARDACIAR 10 (resistance), KW 411 (moderate resistance) and RCC 72 (susceptible) were tested. Pod samples of the clones were harvested in three different plants referring to pod age of 3.0; 3.5; 4.0; 4.5; and 5.0 month. Each pod was seized on the tissue at three different points of middle pod for analysis of trichome density, number of the distributed granule of tannin in mesocarp and lignification at sclerotic layer using microchemical technique in microscopic assessment. The pod development significantly affected the expression of tannin granule and it was described qualitatively of the effect to intensity of lignification at sclerotic layer. KW 514 and KW 411 performed the highest number of tannin granule, namely 1.13 and 1.11 per mm2 and the performance decreased linearly during pod development. The significant decrease was expressed at 3.5–4.0 month of pod age. It was identified a trend of linear decrease for trichome density and KW 411 performed the highest density of the trichome, namely 7.14 each mm which was expressed maximally at 3.0 month of pod age. The sclerotic layer of ARDACIAR 10 was lignified earlier and the tissue show more compact than KW 411 and RCC 72. This result indicated that the optimal expression of CPB resistance was performed at the pod age of 3.0–4.0 month. Key words: Theobroma cocoa L., pod development, resistant characteristics, cocoa pod borer.